(untitled) (Bangladesh Journal of Radiology and Imaging, 2026)
A large intrathoracic myelomeningocele, a saccular protrusion of the meninges through a dilated intervertebral foramen or a bony defect of the vertebral column was diagnosed in a 57-year-old male patient showing clinical features of neurofibromatosis-1 (NF-1). Due to rare entity of this disease at first it presented as pleural effusion seen in initial ultrasound. On detailed investigation it was revealed as a giant intrathoracic myelomeningocele